CORELLATION OF SELF-CONCEPT, ATTITUDE AND CHIEVEMENT MOTIVATION WITH TEACHERS PERFORMANCE IN DISTRICT ILIR TIMUR I PALEMBANG CITY - Alsubiatun, Arif Armadani; Iyakrus, Iyakrus; Sukirno, Sukirno (Sriwijaya University Learning and Education International Conference, 2018)
The objectives of this study were to find out: the relationship between self-concept and the performance of sports teachers, the relationship of attitudes with the performance of sports teachers, the relationship of achievement motivation with the performance of sports teachers, the relationship of self-concept, attitudes and achievement motivation together with the performance of sports teachers. This research was carried out at the Upper High School and Vocational High School (SMA / SMK) in the Ilir Timur 1 subdistrict of Palembang City on April 16, June 16, 2018. Research data collection techniques using questionnaire. Test the validity of the instrument using the product moment formula. Reliability testing uses the Spearman Brown formula. Test The research method used is with multiple correlation techniques resumed with multiple regression with three independent variables. The results of the study show; 1) Self concept with the performance of sports teachers in IlirTimur District 1 Palembang, the amount of Relationship contribution is 96% while the rest is influenced by other variables. 2) attitudes with the performance of sports teachers in Ilir Timur 1 Sub-district, Palembang, the amount of the contribution of the relationship of the remaining 2% is influenced by other variables. 3). Teacher's achievement motivation with the performance of sports teachers in the Ilir Timur 1 Subdistrict in Palembang. The amount of the relationship contribution of the remaining 28% is influenced by other variables. Results and simultaneously 98%, the regression significance is obtained Ý = -11,425+0.960X1+ 0,020X2+0,028X3.